2016
DOI: 10.1038/srep25657
|View full text |Cite
|
Sign up to set email alerts
|

Osthole inhibits histamine-dependent itch via modulating TRPV1 activity

Abstract: Osthole, an active coumarin isolated from Cnidium monnieri (L.) Cusson, has long been used in China as an antipruritic herbal medicine; however, the antipruitic mechanism of osthole is unknown. We studied the molecular mechanism of osthole in histamine-dependent itch by behavioral test, Ca2+ imaging, and electrophysiological experiments. First, osthole clearly remitted the scratching behaviors of mice induced with histamine, HTMT, and VUF8430. Second, in cultured dorsal root ganglion (DRG) neurons, osthole sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…As the most common pruritogen, histamine can produce itch associated with wheal and flare in human skin (Sun and Dong, 2016). Yang et al (2016) recently reported that osthole inhibited histamine-induced acute itching. To further confirm the effect of osthole on acute histamine-dependent itch, we adopted a pretreatment by intradermal injection with osthole into the mouse neck before injection with histamine into the same site.…”
Section: Inhibition Of Trpv3 Channel By Natural Coumarinmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most common pruritogen, histamine can produce itch associated with wheal and flare in human skin (Sun and Dong, 2016). Yang et al (2016) recently reported that osthole inhibited histamine-induced acute itching. To further confirm the effect of osthole on acute histamine-dependent itch, we adopted a pretreatment by intradermal injection with osthole into the mouse neck before injection with histamine into the same site.…”
Section: Inhibition Of Trpv3 Channel By Natural Coumarinmentioning
confidence: 99%
“…Many studies on C. monnieri have focused on antipruritic action of the extracts as well as the ingredients purified from the plant extracts in rodent animal models. Yet, the critical ingredients from the C. monnieri plant used for antipruritus and their mechanisms of action still remain elusive, although Yang et al (2016) recently reported that osthole inhibits capsaicin-induced calcium influx and inward TRPV1 current in cultured small dorsal root ganglion neurons in which other TRPs channels are also expressed (Kittaka and Tominaga, 2017).…”
Section: Osthole Attenuates Pruritus Through Selective Inhibition Of mentioning
confidence: 99%
“…Notably, osthole significantly reduced intracellular Ca 2+ mobilization induced by the MRGPRX2 ligands. Several previous studies have suggested that osthole can block Ca 2+ channels to affect cellular responses (62)(63)(64). For example, a recent study by Su et al, (62) showed that osthole can inhibit neuropathic pain behaviors through inhibition of T-and L-type Ca 2+ currents in nociceptive DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study by Su et al, (62) showed that osthole can inhibit neuropathic pain behaviors through inhibition of T-and L-type Ca 2+ currents in nociceptive DRG neurons. Additionally, osthole blocks TRPV channels to prevent pruritis and dermatitis in animal models (63,64). While it is still unclear whether MRGPRX2 responses in mast cells function via the T-and L-type or TRPV channels, it is plausible that osthole inhibits mast cell activation by blocking these channels resulting in reduced downstream responses such as degranulation and cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, we have paid great attention to the mechanisms of traditional Chinese medicine in the relief of itch. We have found that osthole, an active coumarin isolated from herb Cnidium monnieri (L.) Cusson, which has been long used in China as an antipruritic herbal medicine, inhibits histamine-dependent itch by modulating TRPV1 activity [11]. However, osthole has no effect on the histamine-independent pruritus, limiting its clinical application.…”
Section: Short Communicationmentioning
confidence: 99%